Program Intervensi Dini Bersumberdaya Keluarga dalam Meningkatkan Aspek Bina Wicara Anak Tunarungu - Dira Rosalia Nurkholifah; Agni Nurfadilah; Naurah Rohadatul 'Aisy; Hilmi Maulid Datul Hasanah; Endang Rochyadi (Hayati : Jurnal Pendidikan, 2025)
This study aims to describe the implementation of a family-based early intervention program in improving aspects of speech development in children with hearing impairment. The research method used is descriptive qualitative with a case study approach. The research subjects consisted of early children with hearing impairment and his family who were actively involved in the intervention program at SLB Negeri Cicendo Bandung City. Data collection techniques include observation, interviews, documentation of subject profiles and family profiles, and documentation of program implementation. The instruments used include the child's language-communication development assessment instrument, Kubler Ross parental acceptance instruments, family quality instruments based on Family Quality of Life (FQoL), and records of the implementation and evaluation of intervention programs. The results showed that active family involvement in activities such as oral motor, breathing, and articulation exercises had a positive influence on children's speech development. This is indicated by the subject's improved speech development skills, although continued support from the family is still needed. The implication of this study leads to the importance of active family involvement in the intervention process for the optimization of child development.